Japanese tourists in Victorian Britain: Japanese women and the British heritage industry. Issue 1 (2nd January 2020) - Loh, Waiyee
ABSTRACT: This article explores Japanese women's engagements with the British heritage industry in the 2000s by reading two recent Japanese texts concerned with commodified British heritage, especially heritage from the Victorian period. Reading these Japanese 'heritage texts' reveals that a perceived lack of aristocratic cultural capital, which has grown out of Japan's encounter with informal British imperialism in the nineteenth century, continues to shape young Japanese women's avid participation in the British heritage industry. In the second half of the nineteenth century, British merchants brought material goods and the cultural practices associated with these goods to Japan through trade. On the other hand, Japanese officials and students travelled to Britain to learn from British civilisation at its source. This history has given rise to a longstanding Japanese 'aspiration' ( akogare ) to emulate Britain. The Japanese manga and magazine publishing industry in the 2000s reaffirms these sentiments but also exploits them to its own advantage, by channelling young Japanese women's perception of their cultural belatedness into the buying of both British heritage commodities and the Japanese 'heritage texts' that promote these commodities.